Design of the Arizona CoVHORT: A Population-Based COVID-19 Cohort - Catalfamo, Collin J.; Heslin, Kelly M.; Shilen, Alexandra; Khan, Sana M.; Hunsaker, Josh R.; Austhof, Erika; Barraza, Leila; Cordova-Marks, Felina M.; Farland, Leslie V.; Garcia-Filion, Pamela; Hoskinson, Joshua; Jehn, Megan; et al. (Frontiers in Public Health, 2021)
• This study is a prospective, population-based cohort of individuals with a history of SARS-CoV-2 infection and those without past infection through multiple recruitment sources. The main study goal is to track health status over time, within the diverse populations of Arizona and to identify the long-term consequences of COVID-19 on health and well-being. • A total of 2,881 study participants (16.2% with a confirmed SARS-CoV-2 infection) have been enrolled as of December 22, 2020, with a target enrollment of 10,000 participants and a planned follow-up of at least two years. • This manuscript describes a scalable study design that utilizes wide range of recruitment sources, leveraging electronic data collection to capture and link longitudinal participant data on the current and emerging issues associated with the COVID-19 pandemic. • The cohort is built within a collaborative infrastructure that includes new and established partnerships with multiple stakeholders, including the state’s public universities, local health departments, tribes and tribal organizations. • Challenges remain for ensuring recruitment of diverse participants and participant retention, although the electronic data management system and timing of participant contact can help to mitigate these problems.